2015
DOI: 10.2147/ijn.s82091
|View full text |Cite
|
Sign up to set email alerts
|

Novel stable cytokine delivery system in physiological pH solution: chitosan oligosaccharide/heparin nanoparticles

Abstract: Background Cell therapy is a promising strategy for tissue regeneration. Key to this strategy is mobilization and recruitment of exogenous or autologous stem/progenitor cells by cytokines. However, there is no effective cytokine delivery system available for clinic application, in particular for myocardial regeneration. The aim of this study was to develop a novel cytokine delivery system that is stable in solution at physiological pH. Methods Four groups of self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…the osteogenic effects is complex, mainly owing to the reversible, noncovalent interactions between heparin and heparin-binding GFs, which ensure minimal impact on GF structure. 13,30,37,39,43,44,[48][49][50][51][52] We demonstrated that the nanocomplexes in our study not only effectively loaded and sustained release of PlGF-2/BMP-2, but also maintained their bioactivities for bone regeneration. A key result in this study was the bioactivity of the released PlGF-2 being comparable to that of the released BMP-2, despite its dose being half that of BMP-2.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…the osteogenic effects is complex, mainly owing to the reversible, noncovalent interactions between heparin and heparin-binding GFs, which ensure minimal impact on GF structure. 13,30,37,39,43,44,[48][49][50][51][52] We demonstrated that the nanocomplexes in our study not only effectively loaded and sustained release of PlGF-2/BMP-2, but also maintained their bioactivities for bone regeneration. A key result in this study was the bioactivity of the released PlGF-2 being comparable to that of the released BMP-2, despite its dose being half that of BMP-2.…”
supporting
confidence: 52%
“…29,30 To prepare heparin-HTCC nanocomplexes, heparin and HTCC powder were first dissolved in deionized water to obtain a final concentration of 2 mg/mL of each. Then, the two aqueous solutions were sterilized by passing them through 0.22 μm syringe filters, followed by adding the heparin solution dropwise to the HTCC solution (volume ratio of heparin:HTCC =3:5) with continuous stirring.…”
Section: Preparation and Characterization Of Heparin-based Nanocomplexesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was used to target drugs in vivo to the sciatic nerve, and such system showed no inflammation issues and good biocompatibility, although the authors mention that nerve regeneration is the topic that will be a follow-up to this research [95]. Bone and tissueoriented studies have been worked on, too, for example, bone formation [96] and scaffold [97]; tissue engineering [98]; and regeneration [99]. Some other potential applications that are understudied are as follows: antimicrobial activity [100,101], glucose biosensing [102], analyte detection in solution using a colorimetric approach [103], and surface enhanced Raman spectroscopy [104].…”
Section: Other Potential Applicationsmentioning
confidence: 99%